Kinetics of hepatitis C virus RNA decay, quasispecies evolution and risk of virological failure during telaprevir-based triple therapy in clinical practice. Issue 3 (March 2015) - Cento, Valeria; Tontodonati, Monica; Di Maio, Velia Chiara; Bellocchi, Maria Concetta; Valenti, Fabrizio; Manunta, Alessandra; Fortuna, Serena; Armenia, Daniele; Carioti, Luca; Antonucci, Francesco Paolo; Bertoli, Ada; Trave, Francesca; et al.
Abstract Background The used first generation protease inhibitors may be hampered by virological failure in partially interferon-sensitive patients. Aim To investigate early hepatitis C virus (HCV)-RNA decay and quasispecies modifications, and disclose viral dynamics underlying failure. Methods Viraemia decay at early time-points during telaprevir treatment was modelled according to Neumann et al. (1998). NS3-sequences were obtained by population-sequencing and ultradeep-454-pyrosequencing. Results 13 treatment-experienced (8 non-responders, 5 relapsers), and two cirrhotic naïve patients, received telaprevir + pegylated-interferon-α + ribavirin. Viraemia decay was biphasic. In all patients, first-phase was rapid and consistent, with a median [interquartile-range] viraemia decay of 2.8 [2.6–3.2] log IU/ml within 48 h. Second-phase decay was slower, especially in failing patients: 3/3 showed <1 log IU/ml decay between 48 h and 2 weeks, and HCV-RNA >100 IU/ml at week 2. Only one patient experiencing sustained viral response showed similar kinetics. By pyrosequencing, mutational freeze was observed in all 15 patients within the first 24 h, but only in patients with sustained response afterwards. Indeed, 2/2 failing patients showed early resistance, as minor (V36A-T54A: prevalence <26% at 48 h) or major (V36M/A-R155K: prevalence, 99.8% at week 2) variants. Conclusions Following telaprevir administration, first-phase HCV-RNA decay is consistent with mutational freeze and limited/no viral replication, while second-phase is significantly slower in failing patients (with appearance of resistance), suggesting the usefulness of early HCV-RNA monitoring.